Determination of lipophilic shellfish toxins in bivalve mollusks by ultra-performance liquid chromatography quadrupole linear ion trap mass spectrometry. (October 2019) - Liu, G Y; Wang, Z H; Ge, K; Song, L; Du, J; Wu, J H; Wang, K; Li, A
Abstract: In the study, a method developed for the determination of lipophilic shellfish toxins in muscular tissues of Ruditapes philippinarum was presented. Lipophilic shellfish toxins contain Dinophysistoxin-1 (DTX1 ), dinophysistoxin-2 (DTX2) and homo-yessotoxins (h-YTX). We used microwave-assisted extraction (MAE) method with methanol as extractant to perform the sample preparation for muscular tissues of Ruditapes philippinarum and analyzed the crude extracts by ultra-performance liquid chromatography quadrupole linear ion trap mass spectrometry (UPLC-MS/MS). The microwave-assisted extraction operational parameters, including extraction temperature and volume, the solvent type and time, were selected detailed about extraction efficiency of lipophilic shellfish toxins from Ruditapes philippinarum muscular tissues. The method recoveries at three different spiked levels proved to be in the range from 50.47% to 94.98%. (<10%). The limits of detection (LOD) of three compounds were between 0.001–0.05μg/kg, and it could meet the requirements for the actual samples. Then, this developed method was applied to actual samples which demonstrated that the method was a useful tool for the rapid quantitative detection lipophilic shellfish toxins. All in all, this determined method shows its good selectivity and sensitivity for the analysis of lipophilic shellfish toxins in tissues of Ruditapes philippinarum.